Barriers to finding and maintaining pet-inclusive affordable housing: Tenant experiences in Houston, Texas - Mascitelli, Tess M.; Graham, Taryn M.; Loney, Lauren; Applebaum, Jennifer W.; Murray, Christa M.; Binns-Calvey, Miranda; Hawes, Sloane M.; Morris, Kevin (Frontiers in Veterinary Science, 2024)
The city of Houston, Texas has a growing deficit of available and affordable rental units for low-income residents. Due to pet policies, the shortage of affordable housing potentially puts renters who own pets at greater risk of housing insecurity. In this qualitative study, we use a community-engaged approach to document the lived experiences of finding and maintaining affordable housing among 24 current, former, and aspiring pet owners. The majority of the participants identified as female, were aged 44–60 years, identified as Black, had a high school education, and were employed full-time or on disability or government assistance. Many expressed having experienced homelessness in the past and/or having lived in several different types of affordable housing over their lifetime. Participants highlighted challenges in finding pet-inclusive affordable housing, emphasized its importance, and discussed issues faced, such as high pet charges, size and breed restrictions, and confusion surrounding pet policies. Landlord relationships and living conditions varied, with safety concerns prevalent. Having one’s pet designated as an Emotional Support Animal made tenants feel safe and secure, knowing they could not be refused, evicted, or otherwise charged extra. Participants shared what is working well and what could be improved. This study concludes with recommendations for fair application and awareness of pet policies in affordable housing, drawing on participating tenants’ experiences and existing efforts for policy and practice improvements.